Dynamics of Mononychellus tanajoa (Acari: Tetranychidae) in Africa: Effects on Dry Matter Production and Allocation in Cassava - Yaninek, John S.; Gutiérrez, A.P.; Herren, H.R. (Oxford University Press, 1990)
Seasonally dense populations of Mononychellus tanajoa (Bondar), feeding on the leaves of cassava, Manihot esculenta Crantz, significantly reduced the leaf, stem, and storage-root dry matter of mite-infested plants. Stressed plants met metabolic demands by remobilizing the dry matter in stems and storage roots; however, the proportion of dry matter allocated between the stems and storage roots did not change. Damage by M. tanajoa reduced the dry matter in storage roots by 10–30% by the end of the dry season and by 25–45% three months into the subsequent wet season, depending on the age of the plant. Renewed plant growth following the dry season compensated for drought effects, but mite-induced dry matter losses persisted or increased until harvest during the subsequent wet season. A multiple regression model for predicting yield shows that cassava planted early in the wet season and harvested following the period of maximum mite damage at the beginning of the dry and wet seasons, produces more than twice as much dry matter as cassava planted later, but harvested at the same time.